LENGTH-WEIGHT RELATIONSHIP AND CONDITION FACTOR OF SOME COMMERCIAL FISH SPECIES IN OGUN STATE COASTAL ESTUARY, NIGERIA - O., Abdul W.; T., Omoniyi I.; O., Adekoya E.; I., Adeosun F.; O., Odulate O.; A., Idowu A.; E., Olajide A.; S., Olowe O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2017)
This study examined the length - weight relationships (LWRs) and condition factors of ten (10) commercially exploited fish species: Elops lacerta, Schilbe mystus, Sardienlla maderensis, Synodontis schall, Tilapia zillii, Mugil cephalus, Hepsetus odoe, Chrysichthys auratus, Chrysichthys nigrodigitatus and Sarotherodon galilaeus in Ogun State coastal estuary, Nigeria. A total of 5,609 fish specimens were collected from the commercial landings during the study. Parameters of LWR, a and b were estimated. Growth pattern, b, ranged between 2.462 ± 0.16 and 3.104±0.05 (r2 = 0.8088 to 0.9976). T. zillii, E.lacerta, S.mystus, M. cephalus, S.schall,C. nigrodigitatus and S. galilaeus exhibited allometric growth pattern as b values were significantly (at 95% Cl) different from 3, while C. auratus, S. maderensis and H. odoe exhibited isometric growth pattern ( b value not significantly at 95% Cl). On the average, the growth pattern of fish species sampled was significantly (p<0.05) different from 3. The condition factor, k, ranged from 0.63±0.01 (M.cephalus) to 3.86±0.09 (S. mystus) in the estuary. This indicated that the fish species were in good condition during the study as k values were >0.5. This study, therefore, called for close monitoring of LWR and condition factor of all these commercial fish species for effective stock management in the fishery.